2015
DOI: 10.18632/oncotarget.4810
|View full text |Cite
|
Sign up to set email alerts
|

Triple-layer dissection of the lung adenocarcinoma transcriptome - regulation at the gene, transcript, and exon levels

Abstract: Lung adenocarcinoma is one of the most deadly human diseases. However, the molecular mechanisms underlying this disease, particularly RNA splicing, have remained underexplored. Here, we report a triple-level (gene-, transcript-, and exon-level) analysis of lung adenocarcinoma transcriptomes from 77 paired tumor and normal tissues, as well as an analysis pipeline to overcome genetic variability for accurate differentiation between tumor and normal tissues. We report three major results. First, more than 5,000 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…CELSR3 was found to be highly expressed in ovarian cancer, 4 and hypermethylated in primary oral squamous cell carcinoma, and might be used as a biomarker in OSCC prognostication 10 and small intestinal neuroendocrine tumor. 5 TNXB was reported to be important for the tumorigenesis of lung adenocarcinoma, 6 and was validated as a promising biomarker for early metastasis of breast cancer. 7 TRPM2 was reported to be a potential target of the selective treatment of prostate cancer 11 and was suggested to be a potential therapeutic target in breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…CELSR3 was found to be highly expressed in ovarian cancer, 4 and hypermethylated in primary oral squamous cell carcinoma, and might be used as a biomarker in OSCC prognostication 10 and small intestinal neuroendocrine tumor. 5 TNXB was reported to be important for the tumorigenesis of lung adenocarcinoma, 6 and was validated as a promising biomarker for early metastasis of breast cancer. 7 TRPM2 was reported to be a potential target of the selective treatment of prostate cancer 11 and was suggested to be a potential therapeutic target in breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that silencing of TNX genes promoted malignant transformation in mice [ 32 ]. In addition, TNX genes also could be considered as candidate genes for the distinction between tumor and normal groups in lung adenocarcinoma [ 33 ]. Here, aberrant TNXB DNA methylation was first reported in EC.…”
Section: Discussionmentioning
confidence: 99%
“…The triple-evidenced genes represent the genes that are differentially methylated, differentially expressed and associated with somatic mutation. We found that the triple-evidenced genes shared by a majority of the 13 cancers include many previously identified biomarkers or therapeutic targets [4][5][6][7] . These triple-evidenced genes are enriched in numerous pathways, suggesting possible new targets for therapeutics.…”
Section: Introductionmentioning
confidence: 84%
“…CELSR3 was found to be highly expressed in ovarian cancer 4 , and hypermethylated in primary oral squamous cell carcinoma, and might be used as a biomarker in OSCC prognostication 10 and small intestinal neuroendocrine tumor 5 . TNXB was reported to be important for the tumorigenesis of lung adenocarcinoma 6 , and was validated as a promising biomarker for early metastasis of breast cancer 7 .TRPM2 was reported to be a potential target of the selective treatment of prostate cancer 11 and was suggested to be a potential therapeutic target in breast cancer 12 . TRIP13 promoted early steps of the DNA double-strand break repair and its presence was associated with progression in prostate cancer and squamous cell carcinoma of the head and neck 13,14 .…”
Section: Identification Of Triple-evidenced Genesmentioning
confidence: 99%